NILAI BIMBINGAN PADA SENI RUPA TERAPAN ACEH (ANALISIS SEMIOTIKA RUMOH ACEH) - Adnan, Adnan (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2019)
Aceh is an area in Indonesia which is rich in classical and modern arttreasures, in the form of literary arts, music, dance, and fine arts. Thisresearch specifically aims to uncover, study, and analyze holistically thevalues of guidance in applied arts in Aceh in the form of Rumoh Acehsemiotic analysis. This research method is qualitative-descriptive using anethnographic approach with semiotic analysis techniques. The data of thisstudy were collected through primary sources (in the form of rumoh Aceharchitecture) and secondary, in the form of literature related to thediscussion of this study. The results of the study show: First, rumoh Aceh isan applied art of applied Acehnese society that has practical, aesthetic, andethical uses. Second, rumoh Aceh is an object of applied art that is loadedwith guidance values based on local wisdom in the life of the people ofAceh. Third, the guidance values found in the rumoh Aceh, namelyenvironmentally friendly, disaster mitigation, family resilience,spirituality, and harmony.